2010
DOI: 10.1016/j.jbiomech.2010.07.020
|View full text |Cite
|
Sign up to set email alerts
|

A micromechanical model of skeletal muscle to explore the effects of fiber and fascicle geometry

Abstract: Computational models of muscle generally lump the material properties of connective tissue, muscle fibers, and muscle fascicles together into one constitutive relationship that assumes a transversely isotropic microstructure. These models do not take into account how variations in the microstructure of muscle affect its macroscopic material properties. The goal of this work was to develop micromechanical models of muscle to determine the effects of variations in muscle microstructure on the macroscopic constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 17 publications
(29 reference statements)
2
70
0
Order By: Relevance
“…In future, finite element modelling of whole muscle including fascicles similar to the work of Blemker's group (eg , Sharafi and Blemker, 2010, Blemker et al, 2005) will be necessary to further understand the collagen fibre pressure terms considered in the present work. These works have shown that the finite element approach is effective, for example in confirming the role of muscle force transmission through shear in the connective tissue in the case of terminating fibres and this approach could help to confirm the pressure/hoop-stress hypothesis for passive muscle resistance to external deformation reported in this paper.…”
Section: Limitationsmentioning
confidence: 99%
“…In future, finite element modelling of whole muscle including fascicles similar to the work of Blemker's group (eg , Sharafi and Blemker, 2010, Blemker et al, 2005) will be necessary to further understand the collagen fibre pressure terms considered in the present work. These works have shown that the finite element approach is effective, for example in confirming the role of muscle force transmission through shear in the connective tissue in the case of terminating fibres and this approach could help to confirm the pressure/hoop-stress hypothesis for passive muscle resistance to external deformation reported in this paper.…”
Section: Limitationsmentioning
confidence: 99%
“…To initially validate the approach for defining geometries and boundary conditions, we performed simulations with a muscle to ECM shear modulus ratio ranging from 0.01 to 500 for a healthy muscle fascicle; the results replicated those found by Sharafi & Blemker [26]. The micromechanical model was then used in a parameter analysis to test the individual effect of a number of variations in microstructures prevalent in musculoskeletal disease.…”
Section: Analysesmentioning
confidence: 87%
“…As muscle fibre force is known to be transmitted laterally through shearing of the endomysium, we were interested in analysing the muscle in shear [4,26]. We assigned the boundary conditions to prescribe simple shear deformation, representing the shear displacement of muscle fibres and fascicles relative to each other.…”
Section: Conversion From Agent-based Model To Micromechanical Modelmentioning
confidence: 99%
See 2 more Smart Citations